Carbon clamping cloth capable of efficiently absorbing VOCs (volatile organic compounds) in air and preparation method of carbon clamping cloth
By improving the treatment method and structural design of activated carbon, a carbon clamp cloth that efficiently absorbs VOCs in the air is formed, which solves the problem of insufficient VOCs adsorption capacity of traditional activated carbon in high humidity environments, and achieves higher adsorption efficiency and capacity.
Patent Information
- Application Number
- CN202411614420.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-13
AI Technical Summary
Traditional activated carbon clamp cloth has weak adsorption and purification ability of volatile organic compounds VOCs in an environment of high humidity multi-component gas.
By grinding the mixed liquid of the first activated carbon and water to a uniform distribution, and adding a modifier and a dispersant, after ultrasonic impregnation and dispersion, spraying on the receiving substrate to form a highly absorbent skeleton layer. Then, the second activated carbon is mixed with the activated alumina impregnated with the active component, and a hot melt adhesive mesh film and meltblown cloth are laid in the high-water absorption skeleton layer to form a carbon clamp cloth.
It improves the adsorption efficiency and capacity of the carbon clamp cloth to VOCs in high humidity environments, reduces the airflow resistance, and enhances the hardness and adsorption effect of the material.
Smart Images

Figure CN119455590A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of air purification, and in particular to a carbon-containing cloth capable of efficiently absorbing VOCs in the air and a preparation method thereof. Background Art
[0002] Activated carbon has a large adsorption capacity for various gases, mild operating conditions, low cost, strong regeneration, and is suitable for various environmental operations. It is currently the most commonly used adsorbent for air purification and is widely used in air purifiers. Traditional activated carbon is hydrophobic, which also limits its adsorption and purification capacity for volatile organic compounds (VOCs) in a high-humidity multi-component gas environment.
[0003] Due to the electrical conductivity and chemical reactivity of water, the humidity in the environment needs to be controlled in many fields such as chemical industry and battery to extend the service life of materials and devices; activated carbon has become a good matrix material for composite desiccant due to its well-developed pore structure, large specific surface area and low material cost. Therefore, it is of great significance to improve the hydrophilicity of activated carbon and increase its adsorption efficiency and capacity for gas at a certain humidity. Summary of the invention
[0004] In view of the problem that the conventional activated carbon-coated carbon cloth in the prior art has a weak adsorption and purification ability for volatile organic compounds (VOCs) in a high-humidity multi-component gas environment, the present invention proposes a carbon-coated carbon cloth that can efficiently absorb VOCs in the air and a preparation method thereof.
[0005] The purpose of the present invention can be achieved by the following technical solutions:
[0006] One of the purposes of the present invention is to provide a method for preparing a carbon cloth that can efficiently absorb VOCs in the air, comprising:
[0007] S1, ball-milling a mixture of the first activated carbon and water until the activated carbon particles are evenly distributed, then adding a modifier and a dispersant, and dispersing by ultrasonic impregnation to obtain a spray liquid; spraying the spray liquid on a receiving substrate and drying it, repeating multiple times to obtain a highly water-absorbent skeleton layer;
[0008] S2, mixing the second activated carbon and the activated alumina impregnated with the active component to obtain an adsorption material;
[0009] S3. Lay the first hot melt adhesive mesh on the unsprayed surface of the highly absorbent skeleton layer, continue to lay the adsorbent material flat after hot pressing, then lay the second hot melt adhesive mesh and fix it with hot pressing, and finally lay the meltblown cloth to obtain a carbon-containing cloth that efficiently absorbs VOCs in the air.
[0010] Furthermore, in S1, the first activated carbon is dominated by mesopores and micropores, and the total specific surface area of mesopores and micropores accounts for 75%-85% of the total specific surface area of the activated carbon. The specific surface area of the first activated carbon is 600-800m2 / g of coconut shell activated carbon based carbon.
[0011] Furthermore, in S1, the modifier is a solution composed of one or more solutes selected from CaCl2, MgCl2, and LiCl, preferably CaCl2, and the amount of the solute added is 15 to 30 wt%.
[0012] Further, in S1, the spraying step is specifically as follows: spraying the spraying liquid on the receiving substrate and drying it at 90-100°C for 0.5-1.0h, repeating 2-3 times, so that the loading amount on the receiving substrate is 40-80g / m 2 .
[0013] Further, in S1, the receiving substrate has a gram weight of 60-70 g / m 2 Polyethylene terephthalate (PET) nonwoven fabric.
[0014] Furthermore, in S2,
[0015] The mass of the activated alumina is 10%-20% of the mass of the second activated carbon;
[0016] The particle size of the activated alumina is 0.30-0.40 mm;
[0017] The activated alumina is loaded with active components by equal volume impregnation by ultrasonic method. During the impregnation process, the activated alumina is placed in a 40kHz ultrasonic water bath for 80 minutes, then allowed to stand for 12 hours, heated at 60°C, and continuously stirred until the liquid is completely eliminated. The active component is one of KMnO4, Mn(NO3)2, and K2FeO4 solutions, with a concentration of 0.8-2.0 mol / L, preferably 1.0-1.5 mol / L.
[0018] Furthermore, in S2, the second activated carbon has a specific surface area of 1300m 2 / g, microporous coconut shell activated carbon with a particle size of 0.18-0.25mm and an iodine value of 1200mg / g.
[0019] Furthermore, in S3,
[0020] The first hot melt adhesive web is a hot melt adhesive web composed of one or more of polyolefin (PO), polyethersulfone resin (PES) or polyamide (PA), with a gram weight of 10-15 g / m 2 , melting range is 80-120℃;
[0021] The second hot melt adhesive web is a polyethersulfone resin (PES) hot melt adhesive web with a gram weight of 18-25 g / m 2 , melting range is 80-120℃;
[0022] The meltblown cloth is 25g / m 2 Polypropylene meltblown nonwoven fabric.
[0023] Among them, the second hot melt adhesive mesh has a heavier gram weight than the first hot melt adhesive mesh. This is because the hot melt adhesive mesh with a larger gram weight can maintain stable mechanical properties after hot pressing molding. It has excellent strength and stiffness. While ensuring the fixation of the activated carbon layer, a certain gap can be generated between the carbon layers. The gas will be diverted when passing through the interface layer, reducing the resistance of the airflow through the carbon cloth.
[0024] Furthermore, in S3, the amount of the second activated carbon laid is 180-200 g / m 2 .
[0025] Furthermore, a desktop conveyor is arranged below the highly absorbent skeleton layer and a high-voltage electrostatic powder sprinkler is arranged above it to ensure that the adsorption material can be evenly distributed in the skeleton layer; the powder amount adjustment range of the high-voltage electrostatic powder sprinkler is 25%-35%, and the transmission frequency of the desktop conveyor is set to 15-20Hz, so as to achieve a uniform distribution effect of the adsorption material particles, while avoiding the particles falling from the cloth surface due to excessive amplitude, high frequency, and long time.
[0026] Furthermore, in S3, the hot pressing temperature is 90-110°C.
[0027] The second object of the present invention is to provide a carbon cloth that can efficiently absorb VOCs in the air, which is prepared by the preparation method described above.
[0028] Mechanism of action: Water vapor is adsorbed by activated carbon through different adsorption mechanisms under different conditions. In a high humidity environment, water vapor mainly exists in the form of capillary condensation in the pore structure, while in a low humidity environment, water vapor is mainly chemically adsorbed in the microporous structure. The oxygen-containing functional groups on the surface of activated carbon tend to form hydrogen bonds with water molecules, causing water molecules to easily occupy the adsorption sites of VOCs, thereby reducing the amount of VOCs adsorbed by carbon-based materials. Alumina is added to microporous activated carbon as an active component. Since alumina is a polar adsorbent, it can preferentially react with polar gas molecules such as water vapor and SO2 in the mixed gas during gas treatment, reducing the competitive adsorption of these polar molecules with VOCs on the microporous material, thereby achieving the effect of effectively removing VOCs. The impregnated active component can remove VOCs by chemical adsorption.
[0029] Compared with the prior art, the present invention has the following advantages:
[0030] (1) On the one hand, the carbon cloth material of the present invention has a coconut shell activated carbon with a pore structure dominated by mesopores and micropores and loaded with strong water-absorbing groups arranged upstream of the receiving substrate, so that the material still has high performance in a high humidity environment; on the other hand, the moisture content of VOCs in the mixed gas is reduced after passing through the receiving substrate, and under the action of the active components, it is also helpful for its adsorption on the microporous activated carbon.
[0031] (2) The middle layer of the carbon cloth material of the present invention is made of a PES hot melt adhesive mesh with high rigidity and toughness. The PES hot melt adhesive mesh can maintain stable mechanical properties while being hot-pressed and flow-formed, and has excellent strength and rigidity. It enhances the stiffness of the carbon cloth material while allowing certain gaps to exist in the activated carbon layer, thereby increasing the effective contact area between the gas and the activated carbon layer and reducing the filtration resistance of the carbon cloth material to a certain extent. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 is a comparison chart of toluene removal efficiency changes over time in Example 1;
[0033] Figure 2 It is a comparison chart of the change of toluene removal efficiency over time in Example 1, Comparative Example 1 and Comparative Example 4 under the conditions of 25° C. and 50% RH. DETAILED DESCRIPTION
[0034] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0035] Example 1
[0036] In order to overcome the problem that the conventional activated carbon-coated carbon cloth in the prior art has a weak ability to adsorb and purify volatile organic compounds (VOCs) in a high-humidity multi-component gas environment, this embodiment provides a method for preparing a carbon-coated carbon cloth that can efficiently absorb VOCs in the air, comprising the following steps:
[0037] Step 1: Preparation of the drying layer
[0038] (1) The first activated carbon selected has a pore structure dominated by mesopores and a specific surface area of 650 m 2 / g, the total specific surface area of mesopores and micropores is about 500m 2 / g, coconut shell activated carbon-based carbon with a particle size of 0.25-0.60mm; prepare a 17wt% CaCl2 aqueous solution as an impregnation solution, immerse the first activated carbon in the CaCl2 impregnation solution, ultrasonic temperature 45°C, power 30kHz ultrasonic impregnation for 120min; then dry at 120°C for 2h to obtain impregnated activated carbon; by weight, 10 parts of impregnated activated carbon, 1 part of polyvinyl alcohol and 20 parts of deionized water are ball-milled to form a spray liquid, and the spray liquid D90 is measured by a particle size distribution instrument to be 102nm, and it is transferred to a sprayer for standby use;
[0039] (2) The receiving substrate has a gram weight of 60-70g / m 2 Polyethylene terephthalate nonwoven fabric, fix the receiving substrate on the table with the sprayed surface facing up, laminate the protective film on the unsprayed surface, use a spray pump to spray the receiving substrate, transfer the receiving substrate to an oven at 85°C for 1h after spraying, repeat the above spraying and drying operations 3 times, and weigh and calculate the coating loading to be 40g / m 2 , a highly water-absorbent skeleton layer can be obtained.
[0040] Step 2: Preparation of adsorption materials
[0041] The second activated carbon has a specific surface area of 1300m 2 / g, particle size 0.18-0.25mm, iodine value of 1200mg / g microporous coconut shell activated carbon. The active component is 1.0mol / L KMnO4 solution, the particle size of activated alumina is 0.30-0.40mm; 20g activated alumina is immersed in 100mL active component solution, and the temperature is controlled at 40℃ by ultrasonic dispersion. During the impregnation process, the activated carbon is placed in a 40kHz ultrasonic water bath for 80min, then left to stand for 12h, heated at 60℃, and stirred continuously until the liquid is completely eliminated to obtain impregnated alumina; the second activated carbon is mixed with the impregnated alumina at a mass ratio of 9:1 to obtain the adsorption material.
[0042] Step 3: Preparation of carbon cloth
[0043] (1) After laying a first hot melt adhesive film on the receiving substrate spray layer and hot pressing and fixing it, evenly lay the adsorbent material on the surface, lay a second hot melt adhesive film on the adsorbent material layer and hot press and fix it, and then stack a meltblown cloth on the second hot melt adhesive film, wherein the meltblown cloth has a gram weight of 25 g / m 2 Polypropylene (PP) meltblown nonwoven fabric, the first hot melt adhesive web has a gram weight of 15g / m 2 Polyolefin hot melt adhesive web film, the second hot melt adhesive web film has a gram weight of 20g / m 2 The laying amount of polyethersulfone resin (PES) adsorbent material is 200g / m 2 .
[0044] (2) a desktop conveyor is arranged below the receiving substrate and a high-voltage electrostatic powder sprinkler is arranged above the receiving substrate to ensure that the adsorbent material can be evenly distributed on the receiving substrate, wherein the speed frequency of the desktop conveyor is 15 Hz, and the powder amount adjustment range of the high-voltage electrostatic powder sprinkler is 25%-35%;
[0045] (3) The above-mentioned sequentially stacked materials are pressed into shape by hot pressing, and the hot pressing temperature is controlled at 100° C. to obtain a carbon-containing cloth.
[0046] The carbon cloth material prepared above was cut into a disc filter material with a diameter of 112.9 mm and applied to the toluene gas filtration treatment test. The toluene concentration was 80 ppm (air as the bottom gas), the surface wind speed was 0.1 m / s (the aggregate surface was facing the wind), and the experimental environment was: the temperature was 25 ° C, and the relative humidity was 10%, 30%, 50%, and 70%. The toluene removal efficiency under the environment of time is shown in the curve Figure 1 middle.
[0047] like Figure 1 As shown in Table 1, the carbon cloth can completely remove toluene within 10 min, and then the removal efficiency slowly decreases until it is completely deactivated after 90 min. The adsorption capacity can reach 41 g / m 2 ;pass Figure 1 It can be seen that under a certain humidity environment, the impregnation-modified carbon cloth has a certain improvement in the removal efficiency and adsorption capacity of toluene. This is because water vapor condenses by capillary and gathers in the microporous adsorption center of the upper activated carbon, reducing the competitive adsorption of water vapor and toluene on the activated carbon for the adsorption sites, thereby extending the adsorption time of toluene and obtaining a higher adsorption capacity.
[0048] Comparative Example 1
[0049] Compared with Example 1, the difference is that in step 1, "the modifier is directly mixed with the first activated carbon and then ball-milled", and the rest remains unchanged. The test results are shown in Table 1. Figure 2 It can be seen that in the adsorption environment of 25°C and 50% RH, without impregnation, the modifier failed to effectively combine with the activated carbon, resulting in a reduction in the water absorption sites of the dry layer. Under the same humidity conditions, the toluene adsorption efficiency and adsorption capacity both decreased. This is because the water vapor in the gas condenses in the activated carbon microporous adsorption center by capillary condensation, causing the toluene adsorption sites to be partially occupied, thereby reducing the adsorption efficiency and adsorption capacity.
[0050] Comparative Example 2
[0051] Compared with Example 1, the difference is that in step 1, "the first activated carbon is directly dried after being impregnated with the modifier" and then directly mixed evenly with the "modified adsorption material" in step 2, and the rest remains unchanged. The test results are shown in Table 1.
[0052] Compared with Example 1, the gas removal efficiency and adsorption capacity of Comparative Example 2 are slightly reduced. This is because the diversion effect of the airflow is weakened, the effective contact area between water vapor and the first activated carbon layer is reduced, and the water vapor in the gas exists in the form of capillary condensation in the pore structure of the activated carbon, which will block part of the adsorption channels and weaken the removal efficiency. Due to the presence of water vapor, it occupies the toluene adsorption sites, so that the toluene adsorption capacity will be greatly reduced.
[0053] Comparative Example 3
[0054] Compared with Example 1, the difference is that in step 2, "the second activated carbon does not load the active component", and the rest remains unchanged. The test results are shown in Table 1.
[0055] Compared with Example 1, the adsorption capacity of the material in Comparative Example 3 has been greatly reduced. This is because the active components of the second activated carbon layer can effectively adsorb toluene molecules through chemical reactions, so the presence of the active components can increase the adsorption capacity of the material for toluene; due to the presence of the hygroscopic skeleton layer, there are no water molecules in the gas entering the adsorption layer to compete with toluene for adsorption sites, so the initial adsorption efficiency of the material is similar to that of Example 1.
[0056] Comparative Example 4
[0057] Compared with Example 1, the difference is that in step 1, "the receiving substrate does not load components", and the rest remains unchanged. The test results are shown in Table 1.
[0058] Compared with Example 1, the adsorption capacity of the material prepared in Comparative Example 4 is decreased. The removal of the first activated carbon layer reduces the water absorption sites of the drying layer. Under the same humidity conditions, the toluene adsorption capacity is decreased. This is because the water vapor in the gas is condensed and gathered in the activated carbon microporous adsorption center by capillary condensation, so that the toluene adsorption site is partially occupied, thereby reducing the adsorption efficiency and adsorption capacity.
[0059] Comparative Example 5
[0060] Compared with Example 1, the difference is that in step (2) of step 3, the speed frequency of the desktop conveyor is 15 Hz; in step (3) of step 3, the hot pressing temperature is controlled at 100°C. The test results are shown in Table 1.
[0061] Table 1 Toluene removal efficiency at 50% RH
[0062]
[0063] The above is only a preferred embodiment of the present invention, and does not limit the present invention in other forms. Any technician familiar with the profession may use the above disclosed technical content to change or modify it into an equivalent embodiment with equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the technical solution of the present invention still belongs to the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a carbon cloth for efficiently absorbing VOCs in the air, characterized in that: include: S1, ball-milling a mixture of the first activated carbon and water until the activated carbon particles are evenly distributed, adding a modifier, and dispersing by ultrasonic impregnation to obtain a spray liquid; Spraying the spraying liquid on the receiving substrate and drying it, repeating multiple times to obtain a highly water-absorbent skeleton layer; S2, mixing the second activated carbon and the activated alumina impregnated with the active component to obtain an adsorption material; S3. Lay the first hot melt adhesive mesh on the unsprayed surface of the highly absorbent skeleton layer, continue to lay the adsorbent material flat after hot pressing, then lay the second hot melt adhesive mesh and fix it with hot pressing, and finally lay the meltblown cloth to obtain a carbon-containing cloth that efficiently absorbs VOCs in the air.
2. The method for preparing a carbon cloth for efficiently absorbing VOCs in the air according to claim 1, characterized in that: In S1, the first activated carbon has a specific surface area of 600-800m 2 / g of coconut shell activated carbon based carbon.
3. The method for preparing a carbon cloth for efficiently absorbing VOCs in the air according to claim 1, characterized in that: In S1, the modifier is a solution composed of one or more solutes selected from CaCl2, MgCl2, and LiCl, and the amount of the solute added is 15 to 30 wt%.
4. The method for preparing a carbon cloth for efficiently absorbing VOCs in the air according to claim 1, characterized in that: In S1, the spraying step is specifically as follows: spraying the spraying liquid on the receiving substrate and drying it at 90-100°C for 0.5-1.0h, repeating 2-3 times, so that the loading amount on the receiving substrate is 40-80g / m 2 .
5. The method for preparing a carbon cloth for efficiently absorbing VOCs in the air according to claim 1, characterized in that: In S1, the receiving substrate has a gram weight of 60-70 g / m 2 Polyethylene terephthalate nonwoven fabric.
6. The method for preparing a carbon cloth for efficiently absorbing VOCs in the air according to claim 1, characterized in that: In S2, The mass of the activated alumina is 10%-20% of the mass of the second activated carbon; The particle size of the activated alumina is 0.30-0.40 mm; The activated alumina is loaded with active components by equal volume impregnation through ultrasonic method. During the impregnation process, the activated alumina is placed in a 40kHz ultrasonic water bath for 80 minutes, then left to stand for 12 hours, heated at 60°C, and stirred continuously until the liquid is completely eliminated, wherein the active component is one of KMnO4, Mn(NO3)2, and K2FeO4 solutions with a concentration of 0.8-2.0 mol / L.
7. The method for preparing a carbon cloth for efficiently absorbing VOCs in the air according to claim 1, characterized in that: In S2, the second activated carbon has a specific surface area of 1300m 2 / g, microporous coconut shell activated carbon with a particle size of 0.18-0.25mm and an iodine value of 1200mg / g.
8. The method for preparing a carbon cloth for efficiently absorbing VOCs in the air according to claim 1, characterized in that: In S3, The first hot melt adhesive web is a hot melt adhesive web composed of one or more of polyolefin, polyethersulfone resin or polyamide, with a gram weight of 10-15 g / m 2 , melting range is 80-120℃; The second hot melt adhesive web is a polyethersulfone resin hot melt adhesive web with a gram weight of 18-25g / m 2 , melting range is 80-120℃; The meltblown cloth is 25g / m 2 Polypropylene meltblown nonwoven fabric.
9. The method for preparing a carbon cloth for efficiently absorbing VOCs in the air according to claim 1, characterized in that: In S3, the laying amount of the second activated carbon is 180-200g / m 2 .
10. A carbon cloth for efficiently absorbing VOCs in the air, characterized in that: The invention discloses a novel nanostructured carbon foam prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Carbon clamping cloth for automobile air conditioner filter and preparation method of carbon clamping cloth
CN115888251A
Double-effect carbon clamping cloth material and preparation method thereof
CN117298746A
Collector and collection method for organic solvent, and method for measuring amount of organic solvent
JP2019135466A
Combination filter for air cleaning
KR1020130091115A
Odor absorbing paint and preparation method and use thereof
US20200206718A1